Geochemical characteristics and oil-source correlation in offshore regions. (17th January 2016) - Wu, Z. H.; Wu, Y. H.; Xu, S. Y.; Liu, X. L.; Zhai, L. X.; Li, W. Z.; Wu, Y. X.
ABSTRACT: Traditional geochemical methods to correlate oil and source are not quite fit for too many layers in steep offshore regions. Therefore, more biomarkers and new methods are needed to finish more complicated correlations. Resources in Chengbei Beach zone are generally shallow and high-quality light oil. There are two hydrocarbon source sags and many oil-source layers, and the sources are still disputed. More parameters are used to correlate oil source (i.e., relative group compositions, δ 13 C, steroids, hopanes, and terpenoids). Some special methods are found, such as the triangular chart of aromatic, asphalt, and saturated hydrocarbon, and the comprehensive use of gammacerane, hopance, and tricyclic terpanes. It is found that there are mainly three oil types. The first type mainly derives from source rocks in Es3, the second type from Es1, and the third type is their mixture. These three oil types are found to have regional features.